PENGEMBANGAN MEDIA GAME EDUKASI BERBASIS MODEL PROBLEM BASED-LEARNING UNTUK MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS X MAN 1 MEDAN - Firli Wardahlia; Tiur Malasari Siregar (MES: Journal of Mathematics Education and Science, 2026)
Educational game media developed based on problem-based learning is one alternative designed to help students improve their mathematical literacy skills and understand sequences and series in a more interesting and interactive way. This study aims to examine the validity, practicality, and effectiveness of using media in mathematics learning. The type of research used is development research with the ADDIE research model. This study was conducted at MAN 1 Medan with class X-16 as the subject. The results showed that the use of educational game learning media could improve the mathematical literacy skills of class X-16 students. This was indicated by the results of subject matter expert validation with a percentage of 88% in the ‘highly valid’ category, as well as media expert validation results with a percentage of 89.9% in the ‘highly valid’ category. In addition, the students' response to the media reached 88.4% and was categorised as ‘very practical’, which was also supported by the N-Gain results on the mathematical literacy skills of class X-16 students with a result of 0.710, which falls into the high category, meaning that the educational game media developed is effective for use in learning the material on sequences and series